Pengaruh Permainan Energetik dalam Meningkatkan Keterampilan Gerak Siswa Tunagrahita sebagai Salah Satu Aspek Perilaku Adaptif - Bandi Delphie (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
The aim of this study was to investigate the effects of energetic games on the movement skills of mentally-retarded students. Employing a quasi-experimental design, this study involved 10 mentally-retarded students belonging to seven-year mental age. The data were collected using behavior test measuring movement skills, which were then analyzed using Mann Whitney U-test. The findings suggest that such games had positive effects on the improvement of the movement skills.